Development and Application of a Reference Manual for Diagnosis and Rational Use of Antimicrobial Agents for Outpatient Primary Care (Digestive System Part): A Delphi Study - Wei D; Chang Y; Chen Q; Wang Q; Zhou H; Wu S; Xian X; Cui Z (Infection and Drug Resistance, 2023)
Du Wei,1,* Yue Chang,1,2,* Qi Chen,3,* Qin Wang,4 Hanni Zhou,1,2 Shengyan Wu,1,2 Xiaomin Xian,5 Zhezhe Cui6 1School of Medicine and Health Management, Guizhou Medical University, Guiyang, Guizhou, People’s Republic of China; 2Center of Medicine Economics and Management Research, Guizhou Medical University, Guiyang, Guizhou, People’s Republic of China; 3Pharmacy Department, Guizhou Provincial People’s Hospital, Guiyang, Guizhou, People’s Republic of China; 4Department of Health Education, Tongren Centre for Disease Control and Prevention, Tongren, Guizhou, People’s Republic of China; 5School of Public Health, Guizhou Medical University, Guiyang, Guizhou, People’s Republic of China; 6Guangxi Key Laboratory of Major Infectious Disease Prevention and Control and Biosafety Emergency Response, Guangxi Key Discipline platform of Tuberculosis Control, Guangxi Centre for Disease Control and Prevention, Nanning, Guangxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhezhe Cui, Guangxi Key Laboratory of Major Infectious Disease Prevention and Control and Biosafety Emergency Response, Guangxi key discipline platform of tuberculosis control, Guangxi Centre for Disease Control and Prevention, Nanning, Guangxi, People’s Republic of China, Tel/Fax +86-0771-2518785, Email czz6997@163.com Yue Chang, School of Medicine and Health Management, Guizhou Medical University, Guiyang, Guizhou, People’s Republic of China, Tel/Fax +86-0851-88308118, Email changyue@gmc.edu.cnPurpose: To establish a concise and easy-to-understand reference manual for outpatient primary care providers, promoting correct diagnosis of digestive system diseases and rational antimicrobial use.Methods: The establishment of the manual encompassed two processes: the development of a draft manual and the validation of the manual. The development process was based on a literature review and expert discussion. The manual comprises portions for disease diagnosis and rationality of antimicrobial use. The validation process employed a two-round Delphi technique, collecting consensus through paper-based or mail-based communications. The response of the Delphi group was assessed by the level of authority and commitment of the panelists and the degree of agreement among them. Furthermore, the manual was preliminarily applied among primary care physicians.Results: A total of 29 panelists completed the Delphi working process. They were authoritative in their professional fields with authority coefficients of 0.813 and 0.818 for the two portions of the manual, respectively. The level of commitment of the panelists was measured by response rates, which were 100.00% and 96.67% for Round 1 and 2. After two rounds, a consensus was achieved with the consensus rates for the two portions of the manual being greater than 65% and 70%, respectively. Kendall W-tests had P-values < 0.001 in both rounds. This reference manual provides 200 diagnostic indicators for 29 common digestive diseases and recommendations for the rational use of antimicrobial agents for 13 categories of digestive diseases. The primary care physicians who used the reference manual reported high satisfaction and frequent usage.Conclusion: Based on a collective consensus of professionals, a reference manual has been established, to provide a concise and easy-to-understand guide specifically for physicians and pharmacists in outpatient primary care. It could facilitate rapid learning to improve the accuracy of diagnosis and treatment for digestive disorders.Keywords: primary health care, digestive system, diagnosis, antimicrobial agents, rational drug use, Delphi technique